Dynamic grouping of ongoing activity in V1 hypercolumnsAn example dataset is available at Mendeley dataset. - Rui Zhang; Jiayu Wang; Xingya Cai; Rendong Tang; Haidong D. Lu (NeuroImage)
Summary: Neurons’ spontaneous activity provides rich information about the brain. A single neuron's activity has close relationships with the local network. In order to understand such relationships, we studied the spontaneous activity of thousands of neurons in macaque V1 and V2 with two-photon calcium imaging. In V1, the ongoing activity was dominated by global fluctuations in which the activity of majority of neurons were correlated. Neurons’ activity also relied on their relative locations within the local functional architectures, including ocular dominance, orientation, and color maps. Neurons with similar preferences dynamically grouped into co-activating ensembles and exhibited spatial patterns resembling the local functional maps. Different ensembles had different strengths and frequencies. This observation was consistent across all hypercolumn-sized V1 locations we examined. In V2, different imaging sites had different orientation and color features. However, the spontaneous activity in the sampled regions also correlated with the underlying functional architectures. These results indicate that functional architectures play an essential role in influencing neurons’ spontaneous activity.